A general performance model for parallel sweeps on orthogonal grids for particle transport calculations - Mathis, Mark Michael, 1976- ([publisher not identified], 2000)
There is a growing need to accurately simulate physical systems whose evolution depends on the transport of subatomic particles. It has long been recognized that the huge computational demands of the transport problem mean that practical solution times will be obtained only by the efficient utilization of parallel processing. For example, since estimates place the time devoted to particle transport in multi-physics simulations at 50-80% of total execution time, parallelizing deterministic particle transport calculations is an important problem in many applications targeted by the Accelerated Strategic Computing Initiative of the United States Department of Energy. One common approach to deterministic particle transport calculations is the discrete-ordinates method, whose most time consuming step is the transport sweep which involves multiple sweeps through the spatial grid, one for each direction of particle travel. The efficient parallel implementation of the transport sweeps is the key to parallelizing the discrete-ordinates method. The key contribution of this thesis is a new general model that can be used to compare the running times of transport sweeps on three-dimensional orthogonal grids for various mappings of the grid cells to processors. Our model, which includes machine-dependent parameters such as computation cost and communication latency, can be used to analyze and compare the effects of various spatial decompositions on the running time of the transport sweep. Insight obtained from the model yields two significant contributions to the theory of optimal transport sweeps on orthogonal grids. First, our model provides a theoretical basis that explains why, and under what circumstances, the column decomposition of the current standard KBA algorithm is superior to the 'balanced' decomposition obtained by classic domain decomposition techniques. Second, our model enables us to identify a new decomposition, which we call Hybrid, that proves to be almost as good as and often better than the current standard KBA method. We obtain expressions for the completion time and discuss theoretical results.